Are 16-year-olds able to cast a congruent vote? Evidence from a "voting at 16" initiative in the city of Ghent (Belgium). (February 2020) - Stiers, Dieter; Hooghe, Marc; Goubin, Silke
Abstract: An often used argument against lowering the voting age to the age of 16 is that this age group would lack a sufficiently high level of "political maturity" and therefore would not be able to cast a vote that is in line with their political opinions. In this paper, we use a unique initiative set up by the city of Ghent (Belgium) to invite 16- and 17-year-olds to take part in a mock election to investigate whether adolescents are able to cast an ideologically congruent or "correct" vote. Our results do not show differences in proximity voting between adolescents and adult respondents. Furthermore, we find no evidence of socio-economic stratification in the extent to which adolescents cast a congruent vote. Our conclusion, therefore, is that this recurrent argument against lowering the voting age lacks empirical validity.